Pelatihan Penulisan Naskah Khutbah bagi Pemuda dan Remaja Masjid di Sei Dadap - M. Thohir; Tri Wahyudi Ramdhan (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Quantitatively, there are far fewer preachers who preach through writing than those who use spoken language. Therefore, this article focuses on preaching using written language. Writing, especially printed mass media, if we pay attention in this day and age, there are lots of printed mass media that can be used as propaganda media, such as magazines, newspapers, journals, books, tabloids, bulletins, and so on. Preparing a Friday sermon manuscript is not difficult, because now there are many books containing a collection of sermon manuscripts that are easily available in bookstores or other places. Sermon books in various languages ​​(Arabic, Indonesian, regional languages) on various topics or themes are very easy to obtain nowadays. Therefore, it is not too difficult for a preacher to prepare the text or manuscript of the sermon, if he uses the method of memorizing concepts. Therefore, training will be held here on Friday Sermon Script Writing for Mosque Youth in Bahung Sibatu Batu Village.